KEPEMIMPINAN KEPALA SEKOLAH MEMODERSASI PENGARUH MOTIVASI KERJA DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN MEJOBO KABUPATEN KUDUS - Kasmijan, 11.5202.0031 (Students Journal of Economic and Management, 2013)
This study aims to identify and examine the influence of disciplinary, work ethic on the performance by moderation oragization commitment that takes an objectof primary school teachers in Kudus Regencyict. Sampling was done by purposive sampling technique. From the result of purposive sampling, the sample was used in this study, totaling 135 people. Testing data technique which is used in this study include validity test by factor analysis, reliability test by Cronbach alpha formula, multiple regression analysis, and significance tests, the coeffisien of determination to prove the hypothesis and mediation test. The result showed that the variables of Culture 0rganizational commitment proved to moderating the effect of motivition and work ethic on the performance of elementary school teachers in Kudus regency. Motivation and work ethic has a positive and significant effect on performance. Motivition variable, work ethic and organization commitment to the performance influenced. The remaining is influence by other variables which is not included in the study. Key word : Motivition, work ethic , school culture, performance